Demography and leaf physiology of Cornus drummondii in response to disturbance in tallgrass prairie - Wedel, Emily Rose (Kansas State University, 2019)
The expansion of woody species into grasslands has altered community structure and ecosystem function of grasslands worldwide. Woody encroachment has led to a loss of floristic biodiversity and changes in ecosystem carbon, nitrogen, and water relations. In tallgrass prairie, the increased cover and abundance of woody species is typically attributed to human activities such as decreased fire frequency and increased grazing intensity. Clonal shrubs are of particular concern because of their ability to spread via vegetative reproduction and resprout after fire. The demographic mechanisms that underlie shrub responses to climate history and disturbance are unknown. Here, I measured ramet demography and leaf physiology of the clonal shrub Cornus drummondii in response to disturbance at the Konza Prairie Biological Station. I quantified the growth rate, reproduction, and ramet demography of C. drummondii in response to fire frequency, grazing, and simulated browsing. Fire and grazing increased C. drummondii ramet growth rates, but rates were low across all treatments in response to extreme drought during the summer in 2018. Browsing did not alter ramet growth rates, but it nearly eliminated sexual reproduction. Vegetative reproduction did not differ between treatments. These results highlight the population-level mechanisms of woody expansion in response to disturbance and emphasize the need for multiple pressures to control the spread of clonal shrubs into grasslands. Additionally, I investigated the effects of fire on leaf physiology. I compared gas exchange rates, water use efficiency, and leaf structure of C. drummondii shrubs immediately following burning to shrubs 1-year post-fire. Despite a severe drought in the year of this study, resprouting shrubs had higher photosynthetic rates, stomatal conductance, and transpiration rates. Additionally, burned shrubs had morphological differences with reduced leaf mass per area and decreased leaf dry matter content. These results suggest C. drummondii modifies leaf structure and physiology in response to fire to maximize carbon gain and accelerate growth after fire. Taken together, these studies identify demographic and physiological mechanisms in response to multiple disturbances that contribute to the increased cover of C. drummondii in tallgrass prairie.
Keywords: tallgrass prairie; woody encroachment; plant demography; plant physiology